2007
DOI: 10.1590/s0074-02762007005000016
|View full text |Cite
|
Sign up to set email alerts
|

Lutzomyia (Nyssomyia) whitmani s.l . (Antunes & Coutinho, 1939)(Diptera: Psychodidae: Phlebotominae): geographical distribution and the epidemiology of American cutaneous leishmaniasis in Brazil Mini-review

Abstract: ("caatingas nordestinas" or "savana estépica").

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
2
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 8 publications
5
49
2
12
Order By: Relevance
“…The high frequency of these species corroborates the findings of other endemic regions of Brazil (2). The high frequency of L. (V.) braziliensis coincides with the frequent finding of L. whitmani, a sand fly that can transmit this parasite to humans and domestic mammals (12,13). In contrast, the low frequency of L. (L).…”
supporting
confidence: 68%
“…The high frequency of these species corroborates the findings of other endemic regions of Brazil (2). The high frequency of L. (V.) braziliensis coincides with the frequent finding of L. whitmani, a sand fly that can transmit this parasite to humans and domestic mammals (12,13). In contrast, the low frequency of L. (L).…”
supporting
confidence: 68%
“…whitmani in the peridomiciliary area shows that this species is highly adapted to human conditions, a fact already noted in other regions of Maranhão (Rebêlo et al 1999a,b, Martin & Rebêlo 2006, Leonardo & Rebêlo 2004). This vector has previously been found naturally infected with Leishmania species from the braziliensis complex, which is involved in the cutaneous leishmaniasis transmission in Maranhão (Oliveira-Pereira et al 2006), and in other Brazilian areas as well (Rangel & Lainson 2003, Costa et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…These last authors reported that N. whitmani prevails in areas of red and red-yellow latosoils or nitosoils, which retain higher humidity, whereas N. neivai predominates in more sandy soils, which are well drained and derive from Caiuá arenite. Nyssomyia neivai, which comprised 12.7% of the total sand fl ies collected, has not been found carrying natural L. braziliensis infection in Paraná, and N. whitmani may be the most important species in ACL epidemiology in Brazil (Costa et al 2007). However, the importance of N. neivai should not be underestimated because of its narrow distribution (Marcondes et al 1999, Casanova et al 2005.…”
Section: Discussionmentioning
confidence: 99%